Cytotoxicity and in vitro characterization studies of synthesized Jeffamine- cored PAMAM dendrimers - Ozturk, Kivilcim; Erturk, Ali Serol; Sansozen, Can; Tulu, Metin; Calis, Sema (TAYLOR & FRANCIS LTD, 2014)
The objective of this study is to make comprehensive cytotoxicity evaluation and in vitro characterization of Jeffamine-cored polyamidoamine (PAMAM) dendrimers on L929 cell lines for oral drug delivery purposes. Ester-, amine-and carboxylic acid-terminated PAMAMs were investigated for their cytotoxicity on L929 cells at different generations and concentrations. Cationic surface charge caused highest cytotoxicity on L929 cells, while ester-terminated PAMAMs showed generation-and concentration-dependent toxicity. Anionic dendrimers were determined as the lowest cytotoxic group, and highest generation number presented lowest cellular toxicity. Encapsulation studies were performed with anionic PAMAMs at 2.5, 3.5 and 4.5 generations and different concentrations. Increasing generation number provides greater loaded naproxen amounts and larger particle size. Moreover, formulations provide controlled release at simulated terminal ileum conditions. Consequently, Jeffamine-cored carboxylic acidterminated PAMAMs can be a promising option for oral drug delivery of poorly water-soluble drugs.
Keywords: Cell culture; dendrimer; Jeffamine; naproxen; oral drug delivery; POTENTIAL-DRUG CARRIERS; POLYAMIDOAMINE DENDRIMERS; TRANSEPITHELIAL TRANSPORT; DENDRITIC MACROMOLECULES; DELIVERY; POLYMERS; RELEASE; SURFACE; BIODISTRIBUTION; NANOPARTICLES; Chemistry; Engineering; Pharmacology & Pharmacy